Construcción disciplinar del conocimiento científico - Serna-Montoya, Edgar (Revista Científica, 2015)
This article presents an analysis of the disciplinary construction of knowledge from a perspective of multidimensionality and complexity. A study is made of the social dimensions that encompass the effects of scientific research on human life and social and cultural relations. The socio-cultural aspects of trust, truth, and disciplinarity, and the order and rationality of scientific knowledge are covered in the development, from the perspective of a democratic and socio-responsible science.